2021
DOI: 10.1111/imb.12719
|View full text |Cite
|
Sign up to set email alerts
|

Post‐mating gene expression of Mexican fruit fly females: disentangling the effects of the male accessory glands

Abstract: Mating has profound physiological and behavioural consequences for female insects. During copulation, female insects typically receive not only sperm, but a complex ejaculate containing hundreds of proteins and other molecules from male reproductive tissues, primarily the reproductive accessory glands. The post‐mating phenotypes affected by male accessory gland (MAG) proteins include egg development, attraction to oviposition hosts, mating, attractiveness, sperm storage, feeding and lifespan. In the Mexican fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 131 publications
1
16
0
Order By: Relevance
“…In A. ludens, transcriptomic studies have shown important changes after mating and MAG-injection suggesting that MAGs could be performing functions such as increasing life span in response to stressful environmental factors, (e.g., low humidity or nutrient limitation), as well as dietary detoxification, glucose regulation, and increasing egg production through translation stimulation (Sirot et al, 2021). In A. obliqua, MAG function is unknown, but, based on the results of our study, they do not seem to have an effect on olfactory response.…”
Section: Discussionmentioning
confidence: 99%
“…In A. ludens, transcriptomic studies have shown important changes after mating and MAG-injection suggesting that MAGs could be performing functions such as increasing life span in response to stressful environmental factors, (e.g., low humidity or nutrient limitation), as well as dietary detoxification, glucose regulation, and increasing egg production through translation stimulation (Sirot et al, 2021). In A. obliqua, MAG function is unknown, but, based on the results of our study, they do not seem to have an effect on olfactory response.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti (downregulated), D. melanogaster (upregulated) and the sweet potato white fly B. tabaci (upregulated; [29,39,41] and glyceraldehyde 3 phosphate dehydrogenase is upregulated by mating in Anastrepha ludens (Diptera: Tephritdae) [24]. The lipid biosynthesis pathway is significantly upregulated by mating in A. ludens and genes involved in fatty acid synthesis are upregulated by mating in both A. ludens and Anastatus disparis [24,47]. Fatty acid synthesis contributes to egg development, embryogenesis, fecundity, and digestion in some insects [48,49].…”
Section: A Metabolism-related Genesmentioning
confidence: 99%
“…It is plausible that mating-regulation of CYPs could contribute to detoxification of seminal fluid molecules that impact female survival [23,55,56]. Further, the many proteolysis-related mating-regulated genes are likely to play a role in other processes including: immune response; the activation, inactivation, and/or degradation of seminal fluid molecules; and protection of sperm from proteolytic degradation [24,29,31,39,57]. Together, the regulation of many different genes involved in immunity and detoxification are likely to be involved in the female response to the introduction of foreign substances during the mating process.…”
Section: A Metabolism-related Genesmentioning
confidence: 99%
See 2 more Smart Citations